Ekologi Integral: Alternatif dalam Krisis Lingkungan Hidup - Haward, Ambrosius S. (MELINTAS An International Journal of Philosophy and Religion (MIJPR), 2021)
Today’s ecological crisis is getting worse, and human activities might have been the main cause of the crisis. From a theological point of view, the spiritual crisis among the modern people can be thought of as the source of the devastating human activities. Pope Francis in his encyclical Laudato Si’ believes that mistaken anthropocentrism and technocratic paradigm are the main cause, while theologian Leonardo Boff points on the modern science experimental perspective and the attitude of negligence as the triggering characteristics that govern the modern people. Facing the ecological crisis which has its roots in human spiritual crisis, Pope Francis offers a model of an integral ecology, while Boff offers an eco-spirituality concept, as basis for human relation to the cosmos. Both concepts emphasise on the unity of all components that exist in the cosmos as God’s creation.